"فعالية استخدام ابتكار "بوفيم" B.O.F.I.M في تحسين إتقان تصريف الفعل المضارع لدى طلاب المرحلة الثانوية الدنيا في تعلم اللغة العربية: "The Use of B.O.F.I.M Innovation to Improve Mastery of Fi`il Mudhari’ Conjugation Among Lower Secondary Students" - Mohd Razi, Nur Farah Wahida (SIBAWAYH Arabic Language and Education, 2024)
يُعتبر إتقان تصريف الأفعال، خاصةً في زمن المضارع، أمرًا بالغ الأهمية لطلاب المرحلة الثانوية الدنيا في مواد اللغة العربية. تقدم هذه الدراسة ابتكار بوفيم (لوحة تصريف الفعل) الذي تم تطويره لتعزيز مهارة الطلاب في تصريف الأفعال في زمن المضارع في اللغة العربية من خلال منهجية منظمة. وقد أظهرت الملاحظات أن العديد من الطلاب، لا سيما الذين لم يسبق لهم تعلم اللغة العربية، يواجهون صعوبات كبيرة في إتقان هذه المهارة اللغوية. بناءً على ذلك، تم تصميم ابتكار بوفيم لمعالجة هذه الفجوة. اعتمدت الدراسة على نموذج التصميم التعليمي ADDIE، والذي يتكون من خمس مراحل: التحليل، التصميم، التطوير، التنفيذ، والتقييم. من خلال اتباع هذه المراحل، سعى الباحث لتحقيق أهداف الدراسة وتحسين إتقان الطلاب لتصريف الأفعال. أظهرت النتائج تأثيرًا إيجابيًا لطريقة بوفيم على الطلاب الذين يتعلمون اللغة العربية. وأثبت هذا الابتكار فعاليته عبر مجموعات طلابية متنوعة. استخدمت الدراسة طرقًا تعليمية وجهاً لوجه في الفصول الدراسية، بالإضافة إلى منصات التعليم عبر الإنترنت، مع استخدام اختبارات قبلية وبعدية تم تقديمها عبر منصQuizizz. كما تم استخدام تطبيق WhatsApp لنشر روابط الاختبارات والرموز QR الخاصة بموارد بوفيم. شارك في الدراسة 78 طالبًا، وأظهرت النتائج تحسنًا كبيرًا في مهارات تصريف الأفعال لدى الطلاب. تبرز هذه الدراسة إمكانيات الأساليب المبتكرة في تجاوز التحديات اللغوية في اكتساب اللغة الثانية، مع تسليط الضوء على فعالية بوفيم في تعزيز الكفاءة اللغوية للطلاب. Mastery of verb conjugation, particularly in the present tense, is crucial for lower secondary students in Arabic language courses. This study introduces the B.O.F.I.M (Verb Conjugation Board) innovation, developed to enhance students’ proficiency in conjugating present tense verbs in Arabic through a structured method. Observations revealed that many students, especially those with no prior exposure to Arabic, face significant challenges in mastering this linguistic skill. In response, the B.O.F.I.M innovation was designed to address this gap. The study employed the ADDIE instructional design model, which includes five phases: analysis, design, development, implementation, and evaluation. By following these phases, the researcher aimed to achieve the study’s objectives and improve students’ mastery of verb conjugation. The findings indicate a positive impact of the B.O.F.I.M approach on students learning Arabic. Its effectiveness was demonstrated across diverse student groups. The study utilized both face-to-face classroom instruction and online platforms, incorporating pre- and post-tests administered via Quizizz. WhatsApp was also used to disseminate test links and QR codes for B.O.F.I.M resources. A total of 78 students participated in the study, and the results show significant improvement in their verb conjugation skills. This study underscores the potential of innovative methods in overcoming linguistic challenges in second language acquisition, highlighting the efficacy of B.O.F.I.M in enhancing students’ linguistic competence. Keywords: Arabic Language Learning, Verb Conjugation, Present Tense, B.O.F.I.M Method, Instructional Design